Validity and Reliability of the First Aid Self-Efficacy Scale for School Emergencies - Avsar, Fatma; Karakaya, Ismail (Journal of Pubnursing Sciences, 2025)
Background:  Accidents and injuries are prevalent in childhood. Physical injuries are common reasons for call an ambulance from schools. Teachers and school nurses attempt to create a safe environment in schools. Teachers have not feel enough self-efficacy while they had first aid information. Aims: To develop a valid and reliable scale to evaluate the first aid self-efficacy perceptions of primary school teachers regarding emergency situations that are frequently encountered in schools. Method: A methodological, validity and reliability study was performed. This study that was carried out with 400 teachers. The total samples were randomly divided into exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The final version of the Teachers’ First Aid Self-Efficacy Perceptions Scale (TFSP) scale contained 26 items. Twenty-one items were positive, and four items were negative. Data were analyzed using SPSS20 and LISREL8.7 programs. Results:  The mean age of the total sample was 39.6±9.7. It was determined that 34.8% of teachers were female. The Cronbach’s α coefficient value was 0.937. Kaiser Meyer-Olkin value was 0.922. According to the CFA result, the X2/df was determined to be 2.381. It was determined that the Root Mean Square Error of Approximation (RMSEA) value was 0.08, and the Comparative Fit Index (CFI) value was 0.94.  Conclusion:  The results obtained show that each structure is acceptable. The TFSP scale is a valid and reliable scale. Teachers' first aid self-efficiency level should be increased. The scale is recommended for use by school health nurses and other health professionals when conducting school-based first-aid training programs among primary school teachers. This scale can be used to determine the teacher's first aid self-efficiency regarding emergency situations that are frequently encountered in schools. Health professionals can use it. It is recommended that the scale items be adapted to other languages or cultures.